Metal–Organic Frameworks: Face‐to‐Face Growth of Wafer‐Scale 2D Semiconducting MOF Films on Dielectric Substrates (Adv. Mater. 13/2021). Issue 13 (1st April 2021) - Liu, Youxing; Wei, Yanan; Liu, Minghui; Bai, Yichao; Wang, Xinyu; Shang, Shengcong; Du, Changsheng; Gao, Wenqiang; Chen, Jianyi; Liu, Yunqi
Abstract : 2D metal–organic framework (MOF) films are recognized as a promising candidate for applications in electronics. In article number 2007741, Jianyi Chen, Yunqi Liu, and co‐workers develop a face‐to‐face confinement growth method to obtain high‐quality, conductive Cu2 (TCPP) MOF films directly on various dielectric substrates. The strategy is achieved by pumping Cu 2+ and TCPP cyclically into a micropore interface to produce this growth.